ECONOMIC DYNAMICS IN THE POLITICAL SPOTLIGHT: ANALYZING THE IMPACT OF PRESIDENTIAL AND LEGISLATIVE CAMPAIGNS ON ECONOMIC GROWTH - Sudjono Sudjono; Sukmayadi Sukmayadi; Kadar Nurjaman; Masnilam Hasibuan; M. Al Muhtadin (UIN Sunan Gunung Djati Bandung, 2023)
This article delves into the intricate relationship between political campaigns, specifically presidential and legislative, and their impact on economic growth. Employing a robust analytical approach, the study systematically examines how these political events influence economic dynamics. The research integrates a comprehensive review of economic-political theories and empirical data analysis to assess the extent to which political campaigns affect economic indicators such as GDP growth, investment, and consumer confidence. By correlating election cycles with economic fluctuations, the study offers a nuanced understanding of the interplay between political activities and economic performance. The findings reveal significant insights into the temporal and causal relationships between political campaigns and economic growth, highlighting the role of political stability, policy anticipation, and investor sentiment. This article contributes to the broader discourse on economic-political interactions, providing valuable implications for policymakers, economists, and political strategists. It underscores the importance of considering political factors in economic forecasting and policy-making, especially in periods leading up to major elections.